Identification of a Novel CNV at 8q13 in a Family With Branchio‐Oto‐Renal Syndrome and Epilepsy. (25th March 2019) - Men, Meichao; Li, Wu; Chen, Hongsheng; Wu, Jiayu; Feng, Yong; Guo, Hui; Li, Jia‐Da
Abstract : Objectives: Branchio‐oto‐renal (BOR) syndrome is characterized by branchial defects, hearing loss, preauricular pits, and renal anomalies, whereas patients with all symptoms except renal defects are diagnosed as branchio‐oto (BO) syndrome. BOR/BO is one of the most common forms of autosomal dominant syndromic hearing loss, and EYA1 is the major causative gene. In this study, clinical and genetic analyses as well as auditory rehabilitation were performed in a Chinese family with BOR/BO syndrome. Methods: Three affected individuals from a Chinese family were analyzed by whole exome sequencing (WES) to analyze the single nucleotide variants and copy number variations (CNVs). Whole genome sequencing was used to identify the breakpoints of CNVs; and quantitative polymerase chain reaction was utilized to verify the CNVs. Furthermore, cochlea implantation was performed in one patient to reconstruct hearing. Results: A heterozygous 2.69 Mb deletion at chromosome 8q13 (chr8: 69582185‐72275725) cosegregates with the BOR/BO symptoms in this family, resulting in heterozygous loss of the EYA1 gene. In addition to typical BOR/BO symptoms, epilepsy or gastroesophageal reflux was observed in some patients. Cochlear implantation resulted in significant hearing improvement in one patient. Conclusions: A novel deletion involving the whole EYA1 gene was identified by WES. To the best of our knowledge, epilepsy or gastroesophageal reflux was reported in BOR/BO patients for the first time, which expanded the BOR/BO phenotypes spectrum. Successful auditory rehabilitation can be achieved with cochlear implantations in some BOR/BO patients. Level of Evidence: 4 Laryngoscope, 130:526–532, 2020